Faculty Salary Structure for Publicly Funded Higher Education Institutions of the Russian Federation - Y. V. Dolzhenkova; A. L. Safonov; A. A. Chub (Moscow Polytechnic University, 2022)
There are some serious issues with the recruitment and motivation of the faculty in the publicly-funded higher education of the Russian Federation. They are a significant reduction in the number of teaching staff, a substantial part of the old-age staff, an increase in the total workload and extracurricular work. The most important reason of the described problems is the issue of remuneration. In this regard, the purpose of the study is to suggest some directions for the development of the material remuneration systems for the employees in the publicly funded higher education. The methodological basis of the research are such methods as analysis and synthesis, as well as abstraction and a structurally systematic approach. As a result, it was determined that: 1) unreasonably low official salaries established by professional qualification groups do not provide the reproduction function of wages in full; 2) the differentiation of official salaries for the lecturers of the same qualification level and the position held, due to the size of the financing of budgetary institutions and the remuneration policy of the university, leads to a violation of the principle of "an equal pay for an equal work"; 3) the presence of a large number of incentive payments in the salary structure leads to the "opacity" of wages. The following recommendations are formulated: the salary structure considering the specifics of the publicly funded higher education is justified, methodological approaches to the structure of the official salaries, as well as the incentive and compensation payments are developed.